Exploring factors influencing student silence in EFL classes: A case study at an Indonesian vocational high school - Pratolo, Bambang Widi; Sakti , Muhammad Muzakki Arya; Bao, Dat (Universitas Ahmad Dahlan, 2024)
Research on student silence in English as a Foreign Language (EFL) classrooms has become increasingly important in language learning environments worldwide. This study investigates the factors contributing to student silence in EFL classes at a vocational high school in Indonesia. The research focused on students in an 11th-grade class, adopting a qualitative approach to explore the experiences of silent students. The study was conducted in two stages: observation and interviews. In the initial observation phase, the researcher examined classroom conditions during EFL lessons to identify students who frequently remained silent. Following this, an interview phase was conducted with six students who often displayed silent behavior. Pre-prepared questions were used to gather insights into their perspectives on class participation and the challenges they faced in engaging actively. The findings revealed several factors that contribute to student silence in EFL classes, including anxiety, limited language proficiency, low self-confidence, lack of motivation, and introverted personality traits. Additionally, students reported experiencing difficulties related to understanding the material, maintaining focus, and speaking in class. The study also identified common activities among silent students, such as engaging in side conversations, doodling, using mobile phones, listening to the teacher, reading textbooks, and taking notes. In conclusion, this study provides valuable insights into the phenomenon of student silence in EFL classrooms, highlighting several factors that may hinder student participation. These findings could inform strategies for improving the quality of teaching and learning in EFL settings, with a particular focus on supporting silent students.